ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG DI PASAR KECAMATAN PANGKATAN - Khairun Nisa; M. Sahnan (Universitas Islam Sumatera Utara, 2021)
Many factors influence the income of sellers. This research was aimed to examine the possible factors that affected the amount of income obtained by sellers of Pangkatan Market on Labuhanbatu Regency. This research was categorized as a descriptive research using quantitative method. This research was conducted in Pangkatan Market with 146 population of sellers. The samples in this research were 95 respondents taken by using Proportionate Stratified Random Sampling technique. Meanwhile the method of data collection were using questionnaires and conducting interview. The variables used included business capital (X1), education level (X2), the duration of business practice(X3), working hours (X4) and sellers’ income (Y). The data analysis used was Multiple Linear Regression (OLS) with level of significance of 5%. The result of the research showed that partially the variables of business capital (X1) and working hours (X4) had significant effect to the income of sellers in Pangkatan Market. Meanwhile the variables of education level (X2) and the duration of business practice (X3) partially did not give significant effect to sellers’ income in Pangkatan Market on Labuhanbatu Regency. Next, the variables of business capital, education level, and working hours similarly gave significant influence towards the sellers’ income in Pangkatan Market. The influence was in the percentage of 52,6% and the remaining 47,4% is affected by the other variables.